The rocks are hotter on the other side of the fence: roadside habitats should inform mitigation design - Sisson, Garrett P.; Roosenburg, Willem M. (Frontiers in Ecology and Evolution, 2023)
Maintaining viable populations of large reptiles is often challenging in road fragmented landscapes. While mitigation structures can reduce impacts, few studies have investigated how mitigation success can be affected by roadside habitats. In southeast Ohio, USA, we evaluated mitigation effectiveness for state-endangered timber rattlesnakes (Crotalus horridus) at a new highway in a forested landscape. Road construction created a wide corridor of open canopy habitats (the right-of-way; ROW) containing roadcuts and stone piles. However, exclusion fencing was constructed along the forest-ROW boundary, leaving the open canopy habitats on the road-side of the fence. Over three years, we monitored 6 rattlesnakes using radiotelemetry and found that rattlesnakes repeatedly crossed the fence to access forest-edge and ROW habitats. Rattlesnakes ostensibly crossed through damaged sections of the fence left in disrepair. The ROW was used most intensively by gravid females (n = 2), with their core home ranges overlapping the ROW by more than 50 percent. Despite the fence crossings, all home ranges were bounded by the highway and no rattlesnake road mortality was observed. Operative temperature models revealed that the ROW provided warmer thermal regimes that were rare or unavailable in the forest. On average, field preferred gestation temperatures (Tb = 29.7 ˚C, SD = 1.8) could be attained or exceeded for more than 5 times as many hours per day in the ROW (7.8 hours) than in the forest (1.4 hours). Habitat selection models indicated gravid females selected warmer thermal habitats that were spatially concentrated in the ROW and edge habitats, while non-gravid snakes avoided the ROW beyond the forest edge. Habitat use within the ROW was mostly limited to rocky microhabitat structures, especially riprap stone piles and subsurface rock crevices on roadcuts, which provided buffered thermal regimes with refugia from extreme temperatures during the day and warmer Te through the night. In forested landscapes, we encourage road planners to consider whether new road corridors are likely to introduce basking sites, and if so, maintain those features on the habitat-side of exclusion fencing, and consider restoring basking sites in the surrounding forest to reduce the potential for ecological trap formation.